Prevalence of extended-spectrum beta-lactamase producing Escherichia coli in community-onset urinary tract infections in France in 2013. Issue 2 (February 2016) - Martin, D.; Fougnot, S.; Grobost, F.; Thibaut-Jovelin, S.; Ballereau, F.; Gueudet, T.; de Mouy, D.; Robert, J.; ,
Summary: Objectives: We sought to assess the importance of extended-spectrum beta-lactamase (ESBL) producing Enterobacteriaceae in urinary tract infections in outpatients in France. Methods: Retrospective laboratory based survey analysing susceptibility patterns of Escherichia coli and Klebsiella pneumoniae isolates providing from urines collected from outpatients during three months in 2013. Results: Four hundred and ninety-nine laboratories collected data on 51, 643 E. coli and 3495 K. pneumoniae isolates. The overall proportion of ESBL-producing E. coli was 3.3%. The proportion was higher for males (4.8%) than for females (3.0%) and increased with age: 2% for patients <20 years to 5.4% for those aged >80 years. More than 95% of isolates we susceptible to cefixime, fosfomycin, and nitrofurantoin. In nursing homes, the ESBL-producing E. coli proportion was 12.1%. For K. pneumoniae, the proportion of ESBL-positive isolates was 6.6%, and this proportion increased with age. Data from 2010 collected from a subset of the network showed that the ESBL-producing E. coli proportion was 2.0%. Conclusion: ESBL-producing isolates were rather frequent in urines in French outpatients in 2013. Males and persons residing in nursing homes were at higher risk of ESBL-positive infection. Despite the increase in ESBL-positive isolates, the susceptibility to antibiotics used to treat cystitis remains high. Highlights: Extended-spectrum beta-lactamase (ESBL) in E. coli has been associated with increased treatment failure and cost management. The prevalence of ESBL-producing E. coli in outpatients' urinary samples has increased significantly in France to reach 3.3%. The prevalence of ESBL-producing Klebsiella pneumoniae in the outpatient setting is circa twice than for E. coli . The prevalence of ESBL-producing E. coli in nursing homes is circa 4 times higher than in the outpatient setting. The prevalence of ESBL-producing E. coli in urinary samples increases significantly with patient's age.